#1**+5 **

There was one too many brackets so I may not have answered the question intended.

I also think you may have left out a square of put an extra one in.

$$\\1.2=\frac{0.5*5.08*18*x^2}{x/3}\div(0.5*0.295*18*(1.2+x^2))*\frac{1.2+x}{3}\\

\\1.2=\frac{0.5*5.08*18*x^2}{1}\times \frac{3}{x}\div(0.5*0.295*18*(1.2+x^2))*\frac{1.2+x}{3}\\

\\1.2=\frac{3*0.5*5.08*18*x}{1} \div(0.5*0.295*18*(1.2+x^2))*\frac{1.2+x}{3}\\

\\1.2=\frac{3*0.5*5.08*18*x}{(0.5*0.295*18*(1.2+x^2))} *\frac{1.2+x}{3}\\

\\1.2=\frac{3*5.08*x}{0.295*(1.2+x^2)} *\frac{1.2+x}{3}\\

\\1.2=\frac{5.08x(1.2+x)}{0.295(1.2+x^2)} \\

\\1.2(0.295(1.2+x^2))=5.08x(1.2+x) \\

\\0.354(1.2+x^2))=5.08x(1.2+x) \\

\\0.4248+0.354x^2=6.096x+5.08x^2 \\

\\0=4.726x^2+6.096x-0.4248\\$$

Now you can solve it using the quadratic formula.

Melody
Sep 26, 2014

#1**+5 **

Best Answer

There was one too many brackets so I may not have answered the question intended.

I also think you may have left out a square of put an extra one in.

$$\\1.2=\frac{0.5*5.08*18*x^2}{x/3}\div(0.5*0.295*18*(1.2+x^2))*\frac{1.2+x}{3}\\

\\1.2=\frac{0.5*5.08*18*x^2}{1}\times \frac{3}{x}\div(0.5*0.295*18*(1.2+x^2))*\frac{1.2+x}{3}\\

\\1.2=\frac{3*0.5*5.08*18*x}{1} \div(0.5*0.295*18*(1.2+x^2))*\frac{1.2+x}{3}\\

\\1.2=\frac{3*0.5*5.08*18*x}{(0.5*0.295*18*(1.2+x^2))} *\frac{1.2+x}{3}\\

\\1.2=\frac{3*5.08*x}{0.295*(1.2+x^2)} *\frac{1.2+x}{3}\\

\\1.2=\frac{5.08x(1.2+x)}{0.295(1.2+x^2)} \\

\\1.2(0.295(1.2+x^2))=5.08x(1.2+x) \\

\\0.354(1.2+x^2))=5.08x(1.2+x) \\

\\0.4248+0.354x^2=6.096x+5.08x^2 \\

\\0=4.726x^2+6.096x-0.4248\\$$

Now you can solve it using the quadratic formula.

Melody
Sep 26, 2014